PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN KAWASAN GOA PETENG SEBAGAI DAYA TARIK WISATA DI DESA JIMBARAN KUTA SELATAN KABUPATEN BADUNG - I Kadek Hariyana; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
Abstract Goa Peteng located in Jimbaran. Goa Peteng is a prehistoric cave, there founded relics in the form of Linga and Yoni and statues of the goddess Parvati. Surrounding by beauty scenery around Goa Peteng, it became the main attraction for visitors. Goa Peteng development managed by PT. Teddy Chandra Jaya. Beside Goa Peteng as the main attraction there, Goa Peteng also plans provided travel support facilities such as: restorant, art shops, stage art performances, and outbound tourism such as the flying fox, Jungle tracking, rock climbing. Because Goa Peteng is an ancient heritage sites and there is a sacred worship place, then in development needs to get the support of the surrounding community. Thus, need to do research on public perception of development and supporting Goa Peteng as Tourism object and the perceptions of the visitors of Goa Peteng. The data of this research is qualitative and quantitative data. Qualitative data is data that is not in the form of numbers and cannot be counted as a general overview of the location of the research, public perception, the existence and history of Goa Peteng. Meanwhile, Quantitative data is data in the form of numbers that can be calculated in this case is the growth of tourist arrivals to Bali in last five years. Based on the research results and discussion, it can be concluded the public perception of Goa Peteng development as a tourist attraction in the village of Jimbaran, in Likert scale obtained by calculating an overall average of 4.54 from 100 people. Meanwhile, the perception of tourists to the area development Peteng Goa as a tourist attraction in the village of Jimbaran Likert scale obtained by calculating the overall average 4.52 out of 5 rating.